INTERVENTIONAL SURGICAL CLOSURE OF VENTRICULAR SEPTAL DEFECT - Boltaboyev Alisher Murodiljon o‘g‘li; Shukurova Fotimaxon Tavakkaljon qizi (Web of Journals Publishing, 2025)
Transcatheter closure of a ventricular septal defect (VSD) is a type of heart procedure. It closes a hole between the left and right ventricles of the heart. It does not make a cut (incision) in the chest wall. The heart has four chambers: two upper (atria) and two lower (ventricles). Blood that is high in oxygen flows from the left atrium to the left ventricle and out to the body, where the vital organs use the oxygen. Blood with less oxygen flows from the right atrium to the right ventricle and out to the lungs. There, it picks up more oxygen. Normally, a wall is present between the left and right atria and between the left and right ventricles. A child with a VSD has a hole in the wall between the left and right ventricles. The hole causes blood to flow abnormally from the left ventricle into the right ventricle. As a result, too much blood can go to the lungs. This causes the heart and lungs to work harder.
Keywords: VSD, transesophageal echo (TEE), aneurysma, ventricular angiogram.